2019
DOI: 10.4103/cytojournal.cytojournal_4_19
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thyroid nodules classified as Bethesda category III on cytology and their malignancy rate: An institutional experience

Abstract: Background: Thyroid gland nodules are common and fine-needle aspiration (FNA) is the gold standard for screening those nodules. The Bethesda system for reporting thyroid cytolopathology standardized reporting thyroid nodules aspirations, but atypia of undetermined significance or follicular lesion of undetermined significance (Bethesda category III) was the most controversial category. The aim of our study is to review our institutional experience and analyze the clinical implications of making a diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…Several studies have indicated the AUS/FLUS diagnostic group has posed an ongoing challenge in terms of clinical management [3,5]. Although several patients with AUS/FLUS BSRTC diagnosis undergo a repeat FNAB, wide research has been done focusing on the application of adjunctive molecular testing to enable suitable clinical management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated the AUS/FLUS diagnostic group has posed an ongoing challenge in terms of clinical management [3,5]. Although several patients with AUS/FLUS BSRTC diagnosis undergo a repeat FNAB, wide research has been done focusing on the application of adjunctive molecular testing to enable suitable clinical management.…”
Section: Discussionmentioning
confidence: 99%
“…The Bethesda system accepted to report thyroid cytopathology standardized the reports of TN aspirations; however, the category that attracted the greatest controversy was AUS/FLUS (Bethesda category III) [3,5]. This occurred because follicular lesions without nuclear atypia (i.e., FLUSs) and lesions with nuclear atypia were both integrated into a follicular or a nonfollicular pattern (i.e., AUS) [3,5]. In studies done prior, the AUS/FLUS category in FNAC has been reported to pose the greatest challenge; while the malignancy risk in AUS/FLUS has been estimated in BSRTC to hover between 5% and 15%, institutional data have revealed wide variations [6].…”
Section: Introductionmentioning
confidence: 99%
“…However, among these six categories of TBSRTC, further management is still complicated for the third category. 5 , 6 This category contains heterogeneous lesions assigned to two subgroups: atypia of undetermined significance (AUS) and follicular lesion of undetermined significance (FLUS). 3–6 The prevalence of malignancy within this category ranges from 5% to 37%.…”
Section: Introductionmentioning
confidence: 99%
“…The objective of TBSRTC was to standardize the reporting of FNAC findings and thereby facilitate the communication of results between pathologists and treating physicians that are unambiguous and clinically helpful. Since its inception, it has been demonstrated that TBSRTC improves the quality of FNAC reporting, reducing ambiguous diagnoses and decreasing surgery rates for benign lesions 10 …”
Section: Introductionmentioning
confidence: 99%
“…Since its inception, it has been demonstrated that TBSRTC improves the quality of FNAC reporting, reducing ambiguous diagnoses and decreasing surgery rates for benign lesions. 10 One of the most important features of TBSRTC was the creation of category III. However, the "atypical" category ("atypia of undetermined significance" [AUS] or "follicular lesion of undetermined significance" [FLUS]) continues to cause diagnostic and therapeutic dilemmas.…”
Section: Introductionmentioning
confidence: 99%